Synchronized lower limb kinematics with pelvis orientation achieves the non-rotational shot. Issue 2 (June 2016) - Nakamura, Taishu; Miyoshi, Tasuku; Takagi, Motoki; Kamada, Yasuhisa
Abstract A non-rotational (NR) shot is now a well-known scoring move in soccer. To execute the NR shot, it is necessary to deprive the ball of any rotational forces during the impact phase. To execute the NR shot, it is natural that the force vector acting from the foot would pass through the ball's center of gravity; however, the coordinated motion of the lower limb joint's angular displacement and the pelvis is still unclear. The aim of this study is to estimate the coordinated leg and pelvis motion during the NR shot as compared to that during instep kicking. Four right-leg dominant college league players were asked to perform a NR shot and an instep kick a total of 10 times each. Hip, knee, and ankle joint angular displacements in the sagittal plane and pelvis yaw and roll rotational motions during both types of kicks were calculated with 14 IR reflective markers using a 3D real-time motion analysis system with a 250-Hz sampling. The Euclidean distances of the joint space of the NR shot and the instep kick were also calculated to detect similarities in the coordinated motion of the lower limb. The results showed that the lower limb joint motions in the sagittal plane were not different; however, the pelvis roll and yaw motions were apparently different, and these phenomena could simulate a pendulum motion with changes in both the vertical and horizontal displacements. These results suggest that the coordinated motion of the lower limb joint's angular displacement shows high similarity between the NR shot and the instep kick, and the pelvis roll and yaw synchronized orientation is essential for achieving the NR shot.